An easy microwave-assisted synthesis of C8-alkynyl adenine pyranonucleosides as novel cytotoxic antitumor agents - Dimopoulou, Athina; Manta, Stella; Parmenopoulou, Vanessa; Kollatos, Nikolaos; Christidou, Ourania; Triantakonstanti, Virginia V.; Schols, Dominique; Komiotis, Dimitri (Frontiers in Chemistry, 2015)
We describe the synthesis of C8-alkynyl adenine pyranonucleosides 4, 5 and 8-phenylethynyl-adenine (II), via Sonogashira cross-coupling reaction under microwave irradiation. Compounds 4e and II were less cytostatic than 5-fluorouracil (almost an order of magnitude) against murine leukemia (L1210) and human cervix carcinoma (HeLa) cells, while the same compounds proved to be more active than 5-fluorouracil against human lymphocyte (CEM) cells.